2013
DOI: 10.1248/bpb.b13-00154
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate Inhibits Methotrexate-Induced Gastrointestinal Mucositis in Rats

Abstract: Gastrointestinal mucositis is one of the most prevalent side effects of chemotherapy. Methotrexate is a pro-oxidant compound that depletes dihydrofolate pools and is widely used in the treatment of leukemia and other malignancies. Through its effects on normal tissues with high rates of proliferation, methotrexate treatment leads to gastrointestinal mucositis. In rats, methotrexate-induced gastrointestinal mucositis is histologically characterized by crypt loss, callus fusion and atrophy, capillary dilatation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…In the current work, most of the villi were covered with flattened or cuboidal cells in long term methotrexate treated group (group IV) as previously reported [18]. This might be related to the antimitotic effect of MTX with wide spread apoptosis of the stem cells in the villus tip [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the current work, most of the villi were covered with flattened or cuboidal cells in long term methotrexate treated group (group IV) as previously reported [18]. This might be related to the antimitotic effect of MTX with wide spread apoptosis of the stem cells in the villus tip [16].…”
Section: Discussionsupporting
confidence: 78%
“…This was in agreement with Jahovic et al [21] who found desquamation of surface epithelium in rats treated with MTX. Some authors [5] suggested that this finding was due to the cytotoxic effect of MTX on the intestinal cells while others [18] related it to the inhibition of the cell proliferation in the small intestinal mucosa. The mucosal damage in the present study progressed to ulcer formation in long term methotrexate treated group (group IV).…”
Section: Discussionmentioning
confidence: 99%
“…A previous gastrointestinal study indicated that layers of alginate solution protected against tissue inflammation due to its expansion on the mucosal surface. 9 Although the present study showed no definite data clarifying the mechanism, further in vitro and in vivo studies will help us elucidate the therapeutic mechanism of UPLE-alginate against OA pathogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…Alginate is a naturally abundant and anionic polysaccharide with homopolymeric blocks of (1–4)‐linked β‐D‐mannuronate and its C‐5 epimer α‐L‐gluronate residues. To date, alginate‐based materials have received considerable attention for clinical applications in various fields, including cartilage tissue engineering …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation